Hubungan Motivasi Dengan Kinerja Tenaga Kesehatan di Puskesmas - Nur Qamariyah; Nursyamsiyah Nursyamsiyah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
One of the main factors affecting health performance is their motivation in working. Motivation is a factor that encouragwes a person to perform a certain activity that leads to the achievement of a particular goal. The purpose of this study to determine the relationship between motivation with the performance of health personnel at Puskesmas Ridge Biak Numfor District. This research is an analytic survey research with cross sectional study method population number 55 people. Sample is 55 with purposive sampling tecniue. Data collection and processing using computer program SPSS version 16,0 by using fisher’s exact test. The reault of this research is the reward p=0,038<0,005,it show there is no relation between reward with performance of health worker, kia peer relations p=0,004.<0,005 it there is a relationsip between the co-worker relationship with Perfoemance of health worker, enviromental condition of p=o,ooo<o,oo5it there is reltion between work environment condition with health worker performance. Conclusion in this research is there is there is relation between reward an c0-worker and condition of work environment with performance of health worker. It is suggested to the Ridge Comunity Health Center to furher improve the relationships of good colleagues and increase health facilities and infratructure in providing services so that health workers can improve their performance.